Mycobacterium avium subspecies paratuberculosis (map) infection in dairy catlle in Taman Pertanian Universiti - Abu Bakar Hamzah, Nurul Asikin (2016)
MAP infection or also known as Johne's disease is viewed as one of the most serious and chronic bacterial diseases among ruminants that will indirectly cause economic losses to the farmers This study was conducted to determine the presence of MAP organisms in fecal and antibodies in the serum samples. A total of 129 fecal samples and 43 serum samples were collected from 43 dairy cattle at Taman Pertanian Universiti (TPU) and the samples were used for detection of antigen and antibodies using Ziehl Neelsen acid fast stain and Complement Fixation Test (CFT) respectively. Results from Ziehl-Neelsen acid fast stain technique revealed, 23 (17.8%) out of 129 samples were positive. Meanwhile, no positive result were obtained from CFT using serum samples. This result might be affected by the stages of infection in MAP as the animals might be under Stage I or Stage II where the concentration of antibodies and antigen were assumed to be too low to be detected. As a conclusion, no active infection was detected in the herd tested and serology tests such as CFT provide high specificity and low sensitivity compared to Ziehl-Neelsen stain. Fecal culture remains the best diagnostic method to confirm MAP despite being time-consuming.